Management and monitoring of mixed groundwater and surface water quality in Bechar, Southwestern Algeria - Aymen Atbi; Mohammed Amin Kendouci; Saliha Mebarki (Acque Sotterranee)
Bechar, in southwestern Algeria, depends on two main water sources: groundwater accounts for 80%, while surface water accounts for 20%. The aim of the study is to assess the suitability of water in the Bechar region for drinking and irrigation purposes by analyzing physical and chemical parameters. The results revealed distinct differences in the composition of groundwater and surface water. Surface water was characterized by SO42−, Cl−, Ca2+ and Mg2+ composition, whereas groundwater varied between SO42−, Cl−, Ca2+, and Mg2+ and HCO3−, Ca2+, and Mg2+ types. We classified most groundwater samples as good quality for drinking purposes, while the surface water requires careful quality monitoring. In addition, the quality of irrigation water has been assessed, with groundwater being more suitable and reliable than surface water sources. The study also highlighted significant changes in the chemical properties of water when groundwater is mixed with dam water, including increased pH, reduced concentration of dissolved salt, and effects on mineral concentrations (such as calcium, magnesium) and anions (such as chlorides, sulfates, and nitrates). All these findings highlight the need to improve water resource management and sustainability.